2012
DOI: 10.1111/j.1460-9568.2012.08032.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 is an endogenous modulator of cerebellar development and complex behavior during a sensitive postnatal period

Abstract: Prostaglandins are lipid-derived molecules that mediate the generation of fever in the central nervous system. In addition to their proinflammatory role, prostaglandins also impact neuronal development and synaptic plasticity, sometimes in a sex-specific manner. The cerebellum has a high expression of prostaglandin receptors during development, but the role that these molecules play during normal cerebellar maturation is unknown. We demonstrate here that disrupting prostaglandin synthesis with cyclo-oxygenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 70 publications
(72 reference statements)
3
64
0
Order By: Relevance
“…Across all species that exhibit rough-and-tumble play, including humans, males engage in more frequent and more intense physical contact (108). We found that dysregulation of cerebellar PGE2 production during the second postnatal week by either inflammation or NSAID administration impairs later play behavior but only in males (104). Females naturally play less but their level of play activity can still be reduced (109), indicating the sex difference is not a floor effect.…”
Section: Inflammation In the Cerebellum During A Sensitive Window Impmentioning
confidence: 78%
See 1 more Smart Citation
“…Across all species that exhibit rough-and-tumble play, including humans, males engage in more frequent and more intense physical contact (108). We found that dysregulation of cerebellar PGE2 production during the second postnatal week by either inflammation or NSAID administration impairs later play behavior but only in males (104). Females naturally play less but their level of play activity can still be reduced (109), indicating the sex difference is not a floor effect.…”
Section: Inflammation In the Cerebellum During A Sensitive Window Impmentioning
confidence: 78%
“…Too much PGE2 stunts the growth of the dendritic tree, resulting in an overall reduction in excitatory synapses. Inhibition of PGE2 production by COX inhibitors has the opposite effect, an overall sprouting of the dendritic tree and increase in excitatory synapses(104). …”
Section: Prostaglandins Regulate Cerebellar Developmentmentioning
confidence: 99%
“…[127]. PGE2 plasma levels increased in autistic patients [132] social behaviour in juvenile males but not females [133].…”
Section: Polychlorinated Biphenyls (Pcb)mentioning
confidence: 96%
“…When the pregnant mother is sick, it is unlikely that bacterial or viral molecules directly enter the fetal circulation (except in the case of uterine inflammation); in contrast, the neonate is directly exposed to such molecules after birth. It is also important to recall that PGE 2 , the final effector of fever in the brain is an important signaling molecule in brain development (Dean et al, 2012) and generation of the molecule during a fever could have an impact on developmental trajectories. While there is evidence that some newborn animals do not develop a fever immediately after birth, there is nonetheless an innate immune response to LPS (Bilbo et al, 2005;Pillay et al, 1994;Pittman et al, 1974).…”
Section: Fever Friend or Foe: In Pregnancy And Infancy?mentioning
confidence: 99%